2022
DOI: 10.3390/ma15144768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diamond Burnishing on Fatigue Behaviour of AISI 304 Chromium-Nickel Austenitic Stainless Steel

Abstract: The disadvantages of widely used austenitic stainless steels are their low hardness and relatively low fatigue strength. Conventional chemical-thermal surface treatments are unsuitable for these steels since they create conditions for inter-granular corrosion. An effective alternative is a low-temperature surface treatment, creating an S-phase within the surface layer, but it has a high cost/quality ratio. Austenitic steels can increase their surface micro-hardness and fatigue strength via surface cold working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The combination of maximum force and number of passes minimizes the absolute value of axial compressive stresses. This phenomenon has also been observed in previous studies [14]. The large burnishing force in multi-pass DB significantly increases the thickness of the plastically deformed layer.…”
Section: Regression Analysessupporting
confidence: 88%
See 3 more Smart Citations
“…The combination of maximum force and number of passes minimizes the absolute value of axial compressive stresses. This phenomenon has also been observed in previous studies [14]. The large burnishing force in multi-pass DB significantly increases the thickness of the plastically deformed layer.…”
Section: Regression Analysessupporting
confidence: 88%
“…, respectively. Based on our previous study [14], these values of the radius and feed rate maximize the fatigue limit and microhardness in the SL, while burnishing velocities below min / m 100 (given the heat generated by friction) have little effect on the SI characteristics. Therefore, the burnishing force b F and number of passes n were selected as the governing factors in the present study and were implemented through a one-way working scheme.…”
Section: Db Implementationmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, the DB process significantly decreased the 3D height of the surface roughness. Maximov et al indicated that an increase in the percentage of the martensitic phase leads to higher fatigue strength of the burnished AISI 304 steel [11]. Moreover, the initial characteristics, including the roughness, microhardness, and residual stresses had significant impacts on the surface integrity.…”
Section: Introductionmentioning
confidence: 99%